2012
DOI: 10.1590/s1413-78522012000500002
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaina ou bupivacaina e morfina intra-articular pós reconstrução do LCA

Abstract: ObjectiveReconstructive surgery of the ACL is one of the most commonly performed surgeries today and the control of postoperative pain is part of the priorities of the surgeon. Within the arsenal of analgesia we have the intra-articular application of drugs, and the most studied one is bupivacaine with or without morphine. This study compared the application of bupivacaine with or without morphine with a control group after ACL reconstruction with flexor tendon graft.MethodsForty-five patients were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The results described above are supported by some studies [11][12][13][14][15][16][17][18][19] but not by others. [20][21][22] The conflicting findings may be due to various factors.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…The results described above are supported by some studies [11][12][13][14][15][16][17][18][19] but not by others. [20][21][22] The conflicting findings may be due to various factors.…”
Section: Discussionsupporting
confidence: 48%
“…This quantitative meta-analysis involving 12 RCTs [11][12][13][14][15][16][17][18][19][20][21][22] showed that the combination therapy of single-dose IA bupivacaine and morphine is effective for pain relief after knee arthroscopic surgery. There was no significant difference between the two groups in terms of side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have been done previously to study analgesic efficacy of intra-articular local anesthetics,[ 3 ] morphine,[ 4 5 ] clonidine,[ 6 7 ] dexmedetomidine,[ 8 9 ] etc., with varying results.…”
Section: Introductionmentioning
confidence: 99%